An Open-Label Study of Quetiapine Extended-Release in a Sample of Postpartum Women with Bipolar II Depressive Episode - Misri, Shaila; Abizadeh, Jasmin; B. Eng, Andrea; Albert, Gillian; Ryan, Deirdre; Swift, Elena (Current Psychopharmacology, 2015)
Objectives: This prospective, open-label study investigated the effectiveness of Quetiapine Extended-Release (XR) in the treatment of Bipolar II Depressive Episode and its impact on quality of life in postpartum, non-lactating women. Method: Of the twenty-six women enrolled, fifteen completed the fourteen week study. Quetiapine XR was initiated at 50 mg and titrated up to 300 mg daily. Rating scales: Hamilton and Montgomery-Asberg Depression Rating Scales (HAM-D and MADRS), Quality of Life Enjoyment Satisfaction Questionnaire (QLES- Q), Pittsburgh Sleep Quality Index (PSQI), Clinical Global Impression Severity Scale (CGI-S), Mini- International Neuropsychiatric Interview (MINI). Weight, blood pressure, sexual side effects were recorded. The Wilcoxon signed rank test analyzed changes in scores. Multiple imputation accounted for missing data. Results: By week 12, depression remitted at 137.5 mg of Quetiapine XR while sleep restored at 114.3 mg. By week 14, quality of life was restored and 86.7% of women were asymptomatic. No significant changes occurred in weight or sexual functioning. Side effects were transient. Conclusion: The preliminary findings from this open-label trial of Quetiapine XR appear promising for mitigating depression and anxiety symptoms and restoring quality of life in postpartum, non-lactating women with Bipolar II Depressive Episode. This is currently the only study to prospectively investigate the medication’s efficacy in a postpartum population. Limitations of this study include its small sample size, open-label design, and lack of a control group.
Keywords: quetiapine XR